Motivasi Petani Dalam Penggunaan Pupuk Organik Juara Di Kecamatan Jaten Kabupaten Karanganyar - Adhitya Satria Wardana; Suwarto; Eny Lestari (CV. Multi Kreasi Media, 2023)
Organic farming is an agricultural system that is growing rapidly among farmers. This is because agricultural land has become unproductive due to the use of chemicals since the green revolution movement was carried out. Efforts to restore land productivity by using organic fertilizers. Champion organic fertilizer developed by the Agricultural Training Center. The Agricultural Training Center provides counseling to various regions regarding organic fertilizer champions. The Agricultural Training Center assists in the form of production facilities, namely nitrobacter bacteria. This study aims to determine the factors that form the motivation of farmers in the use of organic fertilizer champions in Jaten District, Karanganyar Regency; analyze the level of motivation of farmers in the use of organic fertilizer champions in Jaten District, Karanganyar Regency; determine the relationship between factors forming motivation with farmers' motivation in the use of organic fertilizer champions in Jaten District, Karanganyar Regency. This method uses a basic quantitative research method with survey techniques and sampling using a census. Jaten Subdistrict was chosen as the research location because Jaten Subdistrict is a Subdistrict whose farmers use organic fertilizer champion with a total of 40 farmers. The data analysis method used was Rank Spearman. The results showed 1) factors forming the motivation of farmers age, formal education, non-formal education, number of family members, social environment, and economic environment. 2) The level of motivation of farmers in the use of organic fertilizer champions is in the high category. 3) Variables that relate the factors forming motivation with motivation are age, formal education, non-formal education, social environment, and economic environment. While the number of family members is not significantly related.